A Comparative Study of Different Advance Control Techniques for Steam Drum Level Control of Boiler - Gautam, Abhinav (My University, 2011)
The largest boilers could justify sophisticated boiler controls earlier, but now high fuel costs and occasional limited fuel availability make it necessary to improve boiler efficiency and minimize costly steam losses and disturbances. Drum level controls have become more important, as the boiler loads are being varied to meet needs, rather than operating at full capacity and wasting fuel and steam. The effects of feed pressure surges and steam flow on drum level dictate more complex controls. This work provides the control of steam drum level using advance control techniques like fractional order PID controller technique and fuzzy logic PID controller technique, to get better response from the system. The control system contains two loops, a feedforward control loop using the steam flow as disturbance signal and cascade control loop using drum water level as measuring signal in primary loop and feedwater pressure as measuring signal in secondary loop. The feedforward controller output signal is summed along with the output of the primary controller to establish the set point for the secondary controller. This scheme is effective because steam flow changes are immediately fed forward to change the final feedwater set point for the control actuator. In this way, feedwater flow tracks steam flow and any disturbances in the feedwater system will be arrested quickly. A comparative study is made on the performance of the fractional order PID controller and fuzzy logic PID controller for getting better control efficiency. From the simulation results and graphs, fuzzy PID controller gives better response than conventional PID controller as there is improvement in control parameters with settling time improved by 0.63 seconds, peak overshoot by 0.57 %, ISE by 0.12 % decrease and ITAE by 9.05 % decrease. Further the response of fractional PID controller is better than both conventional and fuzzy PID controller. The control parameters of fractional PID controller is improved as compared to fuzzy PID controller with settling time improved by 6.36 seconds, peak overshoot by 3.09 %, ISE by 0.14 % decrease and ITAE by 4.99 % decrease. There is a remarkable improvement in the control parameters of fractional PID controller as compared to conventional PID controller with settling time improved by 6.99 seconds, peak overshoot by 3.67 %, ISE by 0.26 % decrease and ITAE by 13.59 % decrease.